Hábitos alimentarios, estado nutricional y riesgo a enfermedades crónicas no transmisibles en los estudiantes de Bromatología y Nutrición Humana de la UNAP - Iquitos, 2024 - Ferreira Silva Teodoro, Neidiane (2024)
The analysis focused on identification the relationship between eating habits and nutritional status and the risk of chronic non-communicable diseases in students of Bromatology and Human Nutrition at UNAP- Iquitos, 2024. Method: Through a study that employs a quantitative, non-experimental approach, a descriptive correlational design of a cross-sectional type was implemented. The sample included 135 students from the professional school of Bromatology and Human Nutrition of the 2nd and 3rd level of study. The statistical analysis was conducted using SPSS version 25, applying the Spearman evaluation test to determine if there is a relationship between the variables. Results: 65.19% of the students had unhealthy eating habits, 31% were overweight (overweight and obesity), and high levels of blood pressure and triglycerides. These findings represent risk factors for the development of non-communicable chronic diseases. Conclusion: A direct relationship was observed between eating habits and nutritional status, as well as the risk of developing non-communicable chronic diseases.